Physicochemical Properties Of Oleogels Made Of Natural Wax With Wheat Germ Oil - Güldemir, Kübra; Bilenler, Tuğça; Karabulut, İhsan (Fırat University, 2023)
In this study, wheat germ oil (WGO) oleogels were produced using WGO at 3%, 7%, and 10% oleogelator concentrations, and the most suitable ratios in terms of structural properties were tried to be determined. Stable gels were obtained with 3% candelilla wax (CDW), 8% carnauba wax (CRW), and 6% rice bran wax (RBW), and the quality properties of the WGO oleogels were determined during storage at 4 and 20 °C for 3 months. The solid fat content (% SFC) of the oleogels measured at 20 and 35 °C increased depending on the oleogelator ratio. According to the results of the rheology analysis, it was determined that the storage modulus (G´) of CDW and RBW oleogels were higher than the loss modulus (G´´), and they have properties of the elastic gel. In this study, as a result of structuring WGO with oleogelation, an alternative product with low cost, high storage stability, viscous at room temperature, and no trans-fatty acid was successfully produced.

Bu çalışmada, buğday ruşeym yağı (WGO) ile %3, 7 ve 10 oleojelatör konsantrasyonlarında WGO oleojelleri üretilmiş ve yapısal özellikler bakımından en uygun oranların saptanmasına çalışılmıştır. Stabil jeller %3 kandelilla vaksı (CDW), %8 karnauba vaksı (CRW) ve %6 pirinç kepeği vaksı (RBW) oranlarıyla elde edilmiş olup, üretilen WGO oleojellerinin 3 ay süresince 4 ve 20 °C’deki depolanmasında kalite özellikleri belirlenmiştir. Oleojellerin 20 ve 35 °C’de ölçülen % katı yağ oranları (SFC) oleojelatör oranına bağlı olarak artmıştır. Reoloji analizi sonuçlarına göre CDW ve RBW oleojellerinin depolama modüllerinin (G?) kayıp modüllerden (G??) büyük olduğu ve elastik jele ait özellikler taşıdıkları saptanmıştır. Bu çalışmada WGO’nın oleojelasyon ile yapılandırılması sonucu düşük maliyetli, depolama stabilitesi yüksek, oda sıcaklığında kıvamlı, trans yağ asidi içermeyen alternatif bir ürün başarıyla üretilmiştir.
Buğday Ruşeym Yağı ile Doğal Vakslar Kullanılarak Üretilen Oleojellerin Fizikokimyasal Özellikleri
Keywords: Food Engineering; Gıda Mühendisliği